2014
DOI: 10.1016/j.ypmed.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different domains of physical activity on cause-specific mortality: A longitudinal study

Abstract: OBJECTIVE: To examine the associations between different domains of physical activity and all-cause, cardiovascular disease (CVD) and cancer mortality. METHODS: Participants (n=17,663, aged 16-92years) of two general population health studies conducted between 1977 and 1993 in Switzerland were included. Physical activity was assessed at baseline in the domains of commuting to work, workrelated physical activity, and leisure-time physical activity (including leisure-time activity level and sport activity). A me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
30
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 28 publications
5
30
1
2
Order By: Relevance
“…While the beneficial effects of this type of physical activity on the cardiovascular system are well documented, the literature regarding occupational physical activity is rather inconsistent . Some studies showed health benefits also for occupational physical activity, but other studies showed no significant effects or even reported detrimental health effects . A meta‐analysis suggests that the risk of CVD increases by 10% for moderate and by 24% for high (vs low) levels of occupational physical activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the beneficial effects of this type of physical activity on the cardiovascular system are well documented, the literature regarding occupational physical activity is rather inconsistent . Some studies showed health benefits also for occupational physical activity, but other studies showed no significant effects or even reported detrimental health effects . A meta‐analysis suggests that the risk of CVD increases by 10% for moderate and by 24% for high (vs low) levels of occupational physical activity .…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland, two cohorts established between 1977 and 1993 have collected information on occupational physical activity and, based on a linkage with the Swiss National Cohort, provide mortality follow‐up until 2015: the National Research Program 1A (NRP1A, community‐based primary prevention of CVD) and the Swiss MONItoring of trends and determinants in CArdiovascular disease (MONICA) study . An earlier publication has reported on the impact of different domains of physical activity on cause‐specific mortality based on these cohorts …”
Section: Introductionmentioning
confidence: 99%
“…Regular engagement in moderate‐to‐vigorous intensity physical activity (MVPA) has consistently been associated with reduced risk of mortality across the lifespan (Löllgen, Böckenhoff, & Knapp, ; Wanner et al, ). A recent review also indicated physical activity is associated with more proximal benefits in the early years, such as motor skill development, bone and skeletal health, better adiposity, cardiometabolic health, cognitive development, and psychosocial health (Timmons et al, ).…”
mentioning
confidence: 99%
“…Since little is known about the long-term 67 effects of earlier PA on later health status, more studies are needed to improve primary 68 prevention strategies. Finally, the importance of addressing all domains, and not only LTPA, has 69 been highlighted, as each domain may have different effects on health (13). This study aims to (1) (14).…”
mentioning
confidence: 99%